Revolutionizing the treatment of intervertebral disc degeneration: an approach based on molecular typing - Shaofeng Chen; Wei Zhang; Yifan Liu; Runzhi Huang; Xiaoyi Zhou; Xianzhao Wei (Journal of Translational Medicine)
Abstract Background Intervertebral disc degeneration (IVDD) is a significant cause of global disability, reducing labor productivity, increasing the burden on public health, and affecting socio-economic well-being. Currently, there is a lack of recognized clinical approaches for molecular classification and precision therapy. Methods Chondrocyte differentiation and prognosis-related genes were extracted from single-cell RNA sequencing and multi-omics data in the Gene Expression Omnibus (GEO) database through chondrocyte trajectory analysis and non-parametric tests. Subsequently, a precise IVDD risk stratification system was developed using ConsensusClusterPlus analysis. The clinical significance of molecular typing was demonstrated through case–control trials involving IVDD patients. Specific inhibitors of molecular typing were predicted using the pRRophetic package in R language and then validated in vitro. Results A stratified model for IVDD, considering chondrocyte differentiation and demonstrating high clinical relevance, was developed using a set of 44 chondrocyte fate genes. Extensive analyses of multi-omics data confirmed the clinical relevance of this model, indicating that cases in the High Chondrocyte Scoring Classification (HCSC) group had the most favorable prognosis, whereas those in the Low Chondrocyte Scoring Classification (LCSC) group had the worst prognosis. Additionally, clinical case–control studies provided evidence of the utility of IVDD molecular typing in translational medicine. A gene expression-based molecular typing approach was used to create a matrix identifying potential inhibitors specific to each IVDD subtype. In vitro experiments revealed that gefitinib, a drug designed for LCSC, not only had protective effects on chondrocytes but also could induce the conversion of LCSC into the HCSC subgroup. Therefore, IVDD molecular typing played a critical role in assisting clinicians with risk stratification and enabling personalized treatment decisions. Conclusion The results of the study have provided a comprehensive and clinically relevant molecular typing for IVDD, involving a precise stratification system that offers a new opportunity for customizing personalized treatments for IVDD.